The role of CSR education on sustainable entrepreneurial intention: development of a theory of planned behavior-based model in higher education - Asti, Arsy Annisa; Elsera, Hilda (International Journal of Enterprise Modelling, 2025)
Corporate Social Responsibility (CSR) education has become a crucial component in shaping responsible entrepreneurial attitudes. Accordingly, Higher Education Institutions (HEIs) have consistently integrated CSR into their academic curricula to foster ethical awareness and sustainability-oriented values among prospective business leaders. In this context, HEIs play a strategic role in cultivating a generation conscious of social responsibility and sustainable development, although research on the influence of CSR education on sustainable entrepreneurial intentions remains limited in the literature. This study aims to examine the effect of CSR education on students’ sustainable entrepreneurial intentions based on the Theory of Planned Behavior (TPB) framework. A quantitative approach was employed using a survey method targeting students currently enrolled in or who have completed CSR-related courses. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that attitude toward behavior and perceived behavioral control significantly affect sustainable entrepreneurial intentions. Conversely, subjective norm does not have a direct effect but becomes significant when moderated by CSR education. These findings reinforce the critical role of CSR education in strengthening pro-social values that encourage more responsible entrepreneurial intentions. This study underscores the importance of integrating CSR education into entrepreneurship curricula to develop future entrepreneurs with a strong orientation toward social and environmental sustainability